A metal-free and recyclable synthesis of benzothiazoles using thiourea as a sulfur surrogate. Issue 13 (25th March 2015) - Yin, Yan; Zhou, Hong; Liu, Xichen; Chen, Haiying; Wu, Fanhong; Zhang, Heng; Tao, Ruiheng; Cheng, Fengkai; Feng, Yangbo
Graphical abstract: Abstract: Using odorless thiourea as the S source, benzothiazoles and asymmetric disulfides could be obtained from thioformanilides through the tandem cyclization/nucleophilic addition/hydrolysis/nucleophilic substitution reaction. Furthermore, the obtained asymmetric disulfides could readily transfer to benzothiazoles after nitro-reduction and amide formation reaction. This metal-free and recyclable synthetic methodology offered a time-efficient, less expensive, and environmentally friendly alternative to multifunctional benzothiazoles.